(untitled) (Mustansiria Dental Journal, 2004)
Ormocer the newly developed organically modified ceramic are interesting and promising materials, and may become an interesting filling material for stress bearing class I restorations. Intra oral conditions can be expected ot be more complex than those achivied ni imploying 37°C distilled water (D. W). ni laboratory. Thirty specimens prepared and stored for 14 days in d.w., corn oil, 50% ethanol and divided ot two groups, polished. A study done to investigate microstructural examination of the actual specimens in the SEM revealed equalization differences in the surface texture between polished and non polished Ormocers ni the different storage media with no cracks formation